Microlearning for Micro-Attention: Strategies for Enhancing Student Focus in High-Distractibility Environments Using Short-Form Educational Media - Vicheka Rith; Amir Raza; Mpho Nkosi (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. Student attention spans are increasingly challenged in digital learning environments characterized by high levels of distraction. Microlearning, with its short and focused instructional units, has been proposed as a pedagogical strategy to address issues of micro-attention and cognitive overload. Despite its popularity, limited empirical evidence exists regarding the effectiveness of short-form educational media in sustaining student focus. Purpose. This study aimed to examine the role of microlearning strategies in enhancing student attention within high-distractibility learning contexts. Specifically, it investigated how different formats of short-form educational media influence learners’ focus, perceived engagement, and knowledge retention. Method. A mixed-method design was employed involving 250 undergraduate students across three Indonesian universities. Participants engaged with microlearning modules delivered through video, infographic, and interactive quiz formats. Quantitative data were collected using attention and retention tests, while qualitative insights were gathered through focus group discussions. Results. Findings revealed that students exposed to short-form interactive quizzes demonstrated significantly higher attention and retention scores compared to those using static infographics or video-based modules. Furthermore, qualitative data indicated that students valued the brevity and interactivity of microlearning content, particularly in environments where distractions were prevalent. Conclusion. This study highlights the potential of microlearning as a strategy for addressing micro-attention challenges in digital classrooms. By leveraging short-form, interactive educational media, educators can design more engaging and cognitively sustainable learning experiences. The results provide practical implications for instructional design in technology-rich and high-distractibility learning environments.